The space of nobility: hierarchy and power in Minas Gerais in the 19th century - Luiz Fernando Saraiva (Revista Maracanan, 2018)
This research addresses to power relations built in the province of Minas Gerais throughout the 19th century, with the central object of analysis the nobleness of the major political groups from Minas Gerais. Starting from a review on Brazilian nobiliary studies, we opted to highlight some of the main theories and intepretive analysis, with the intent to posteriorly deepen the titrations of nobles from Minas Gerais as a powerful indicatory of the construction of power relations in one of the major Brazilian provinces in the 19th century. The analysis on the nobility from Minas Gerais can be revealed as an indicative of settlement processes and construction of power relations on the Brazilian State.